Analysis of Denotative and Connotative Meanings in Body Shaming Texts (Jurnal Bahasa, 2024)
The researcher analyzes the denotative and connotative meanings in body shaming texts in Brunei Darussalam. The objective of this study is to identify, categorize, and compare the denotative and connotative meanings in body shaming texts. The study used qualitative and quantitative descriptive methods, and was carried out in stages, that is, according to certain steps. The data of body shaming texts were taken from the social media application Instagram, from an account named @natartsya. The main question in this study is how to distinguish between denotative and connotative meaning based on the Semiotic Triangle theory by Ogden and Richard. The results of the study found that body shaming texts contain more connotative than denotative meaning. The description and explanation of the connotative meaning exists due to the speaker's imagination, which causes the connotative meaning to function as sarcasm or a figurative in order to be more polite when communicating. The implication of this is that the intended meaning sometimes does not reach the recipient. This study can not only benefit future researchers who want to improve or develop the field of semantics, but also benefit the community in Brunei Darussalam about the latest issues that can be studied as well as to indirectly spread awareness about the issue of body shaming.Keywords: Body shaming, denotative, connotative, Semiotic Triangle theory, concept, referent and symbolFull text: PDF